2000
DOI: 10.2134/agronj2000.925957x
|View full text |Cite
|
Sign up to set email alerts
|

Crop Rotation with Tagetes sp. is an Alternative to Chemical Fumigation for Control of Root‐Lesion Nematodes

Abstract: The root‐lesion nematode (Pratylenchus penetrans Cobb) is a significant pest of many crops in Ontario. For example, more than 25 000 ha of land cropped to flue‐cured tobacco (Nicotiana tabacum L.) is fumigated annually at a mean cost for the fumigant materials alone of $484 ha−1. The objectives of these trials were to develop and evaluate a marigold (Tagetes sp.) rotation cropping system for the biological control of root‐lesion nematodes. In 1995 (site A) and 1996 (site B), field plots of Tagetes patula L. cv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 13 publications
1
34
0
1
Order By: Relevance
“…Field testing has shown that tobacco plants benefited from two years of protection in plots that had grown Tagetes patula (French marigold) or Tagetes erecta (African marigold) cultivars [183]. One of the most active antinematodal agents was identified as α-terthienyl (α-T, 11Ch) [184].…”
Section: Sulfurmentioning
confidence: 99%
“…Field testing has shown that tobacco plants benefited from two years of protection in plots that had grown Tagetes patula (French marigold) or Tagetes erecta (African marigold) cultivars [183]. One of the most active antinematodal agents was identified as α-terthienyl (α-T, 11Ch) [184].…”
Section: Sulfurmentioning
confidence: 99%
“…The data were combined over locations, with replications considered random effects and locations and crops considered as fixed effects, but due to significant location × crop interactions observed for most of the measured characters, mean separations between rotation crop treatments was presented for each location. An exception was made for the dry matter of the rotation crop as Bartlett's test (Snedecor and Cochran 1989) showed homogeneity of error variance among locations and the combined data showed a non-significant location × crop interaction effect. Fisher's protected significant difference (LSD α < 0.05) was used to test treatment means.…”
Section: Discussionmentioning
confidence: 99%
“…In Ontario, the economic threshold for losses to most crops is 1000 P. penetrans kg -1 soil and 50 P. penetrans g -1 dry root. For flue-cured tobacco, the economic threshold level is 500 P. penetrans kg -1 soil (Oltholf et al 1973;Reynolds et al 2000b). Therefore, the locations used were considered to be heavily infested with P. penetrans.…”
Section: Pratylenchus Penetrans Populations During the Rotation Crop mentioning
confidence: 99%
See 1 more Smart Citation
“…In southern Ontario, Canada, T. erecta has been grown as a rotation crop for nematode control in tobacco fields (Reynold et al 2000). Planting T. erecta as an inter-crop between tomato plants has also been found useful in reducing nematode populations, although the efficiency was not as good as that of synthetic nematicide (Vasudevan et al 1997).…”
Section: Case Studies Lutein From Marigoldmentioning
confidence: 99%